Impact of Sleep Deprivation and Coping Abilities on The Psychological Adjustment of Caregivers of The Elderly - Naz, Iram; Ghumman, Mishal Rauf; Shabbir, Aliya (Pakistan Armed Forces Medical Journal, 2022)
Objective: To examine the impact of sleep deprivation and coping abilities on the psychological adjustment of caregivers of elderly.Study Design: Cross sectional analytical study.Place and Duration: Department of Psychology, University of Gujrat, Gujrat Pakistan, from Jan to Jul 2018.Methodology: The caregivers of the elderly were recruited in the study with the caregiving experience of 6 months to 2 years. The respondents with any physical or psychological problems were excluded from the study. The sleep deprivation, coping and psychological adjustment were measured using the Pittsburgh sleep quality index, coping styles scale, scale of adjustment for adults respectively.Results: The data of 200 caregivers of the elderly was analyzed using structure equation modeling. The model fit was established with the p-value of